World of Islam Festival (Londres 1976) : Naissance d’un nouveau paradigme pour les arts de l’Islam - Abdallah, Monia (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2014)
This essay traces the origin and stakes of the association between historical Islamic art and works of contemporary art by artists from Muslim countries. The idea that underpins this association—that there is a form of continuity between these works—first appeared in London in 1976 during the World of Islam Festival. This event laid the foundation for the understanding of Islamic art as a vehicle for cultural continuity, so that contemporary art by artists from Muslim countries came to be seen as an extension of Islamic art and became perceived by many as a contemporary Islamic art, that is to say, the art of the Islamic civilization of today. This article argues that the notion of Islamic civilization that the World of Islam Festival vehiculated continues to be felt in the new paradigm for Islamic art that it initiated. This essay analyzes how this event unintentionally spawned a new model for understanding not only Islamic art, but also Islamic civilization, a civilization that is now once again considered alive.